Augmentation of communicative skills among rural high school students in India - Boobalan, Rathika; Loganathan, Saranraj; Gyamfi, Abraham (Frontiers in Education, 2024)
This paper aims to focus on government school students, who struggle hard to express themselves in English. A two-group simple randomized design was used for this study and an experimental study was carried out among sixty rural high school students. 'Captivating Activities' (Listening, Speaking, Reading, and Writing) have been used to find the effect of on learners' communication skills. Furthermore, a pretest and a post test was conducted between groups and their scores were analyzed. A paired sample T-test was carried out to identify the difference between controlled, and experimental groups. The result showed that there was a significant average difference observed between pre and post-test scores (t28=8.327, p=0.000, p<0.01) of the experimental group. As an outcome of a tested strategy, it was understood that English speaking ambience helps students to some extent to pick up that language. It was concluded that the captivating activities (Listening, speaking, reading and writing) are effective for augmenting learners' communication skills.